2022
DOI: 10.1007/s11356-022-24066-6
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment, stock market capitalization, and sustainable development: relative impacts of domestic and foreign capital

Abstract: It is well acknowledged that achieving sustainable development goals without negatively impacting a country's economic activity is complicated. The question of whether foreign or domestic capital can be used to address the financial demands of the nations who lack the financial resources for a green transformation should now be resolved. Based on this, the main goal of this research is to analyze the impacts of domestic and foreign capital on carbon emissions for a heterogeneous panel of 42 countries for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 96 publications
(83 reference statements)
1
1
0
Order By: Relevance
“…When all findings are taken into account, it is discovered that economic expansion causes environmental harm in transition economies. This finding validates the studies of Shahbaz et al (2018); Zafar et al (2022); Destek et al (2021); Adedoyin et al (2021); Adebayo et al (2021); Caglar et al (2022); Destek et al (2022); Liu et al (2022); Manga et al (2023). The fact that real national income growth causes both short- and long-term environmental deterioration indicates that a parabolic connection, or a Kuznets-type relationship, is not yet relevant for transition economies.…”
Section: Empirical Findings and Discussionsupporting
confidence: 86%
“…When all findings are taken into account, it is discovered that economic expansion causes environmental harm in transition economies. This finding validates the studies of Shahbaz et al (2018); Zafar et al (2022); Destek et al (2021); Adedoyin et al (2021); Adebayo et al (2021); Caglar et al (2022); Destek et al (2022); Liu et al (2022); Manga et al (2023). The fact that real national income growth causes both short- and long-term environmental deterioration indicates that a parabolic connection, or a Kuznets-type relationship, is not yet relevant for transition economies.…”
Section: Empirical Findings and Discussionsupporting
confidence: 86%
“…Recent research with a focus on FDI aligning with environmental, social, and governance considerations provides a comprehensive outlook on the impact of FDI on economic growth (Destek et al, 2023). Studies revealed the understanding of the relationship between FDI and economic growth.…”
Section: Morgan Journal Of Interdisciplinnary Research Studiesmentioning
confidence: 99%
“…The environmental effectiveness of domestic capital accumulation is higher in lowemission sates than in high-emission staes. On the other hand, foreign capital does not significantly impact emission levels in all quantiles (Destek, 2023). A study (Shehzad et al, 2021) examined the impact of Objective Oriented Investment Behavior (OOIB) and Financial Risk Attitudes (FRA) on the investors of Pakistani.…”
Section: Literature Reviewmentioning
confidence: 99%